Prescribing competency assessment for Canadian medical students: a pilot evaluation - Holbrook, Anne; Liu, J. Tiger; Rieder, Michael; Gibson, Michelle; Levine, Mitchell; Foster, Gary; Perri, Dan; Maxwell, Simon (Canadian Medical Education Journal, 2019)
Background: The knowledge and ability to prescribe safely and effectively is a core competency for every graduating medical student. Our previous research suggested concerns about medical student prescribing abilities, and interest in a standardized assessment process. Methods: A multi-year cross-sectional study evaluating the feasibility, acceptability, and discriminative ability of an online prescribing competency assessment for final year Canadian medical students was conducted. Students at nine sites of four Ontario medical schools were invited to participate in an online one-hour exam of eight domains related to prescribing safely. Student feedback on perceived fairness, clarity, and ease of use formed the primary outcome. Exam performance and parity between schools were the secondary outcome. Results: A total of 714 students completed the assessment during spring final review courses between 2016 and 2018. Student feedback was more favourable than not for appropriateness of content (53.5% agreement vs 18.3% disagreement), clarity of questions (65.5% agreement vs 11.6% disagreement), question layout and presentation (70.8% agreement vs 12.2% disagreement), and ease of use of online interface (67.1% agreement vs 13.6% disagreement). Few (23.6% believed their course work had prepared them for the assessment. Mean total exam score was 70.0% overall (SD 10.4%), with 47.6% scoring at or above the pass threshold of 70%. Conclusion: Our prescribing competency assessment proved feasible, acceptable, and discriminative, and indicated a need for better medical school training to improve prescribing competency. Further evaluation in a larger sample of medical schools is warranted.